Peltier modules SP1848 in the modes of heat transfer and electrical energy generation and their practical application - Maxim A. Sablin; Galina V. Sablina; Vitaliy G. Trubin (Известия Томского политехнического университета: Промышленная кибернетика, 2024)
This article discusses the problem of studying the properties of the SP1848 Peltier modules (heating, cooling and generating). The first goal was to construct the laboratory stand, which will allow conducting experiments on heating the module, cooling it, and generating electrical energy. It was shown that in the cooling mode the minimum temperature of the module surface was –12.5°C, and in the heating mode the maximum temperature was +69.1°C. Heating the module surface to +120°C provided an output voltage of 2.4V. This voltage was enough to light a 2.5V incandescent lamp. The next goal was to construct a portable refrigerator based on six SP1848 modules and conduct experiments to study its cooling properties. It is shown that Peltier modules make it possible not only to maintain a fixed temperature in the chamber, but also to lower it to certain values. In conclusion, the advantages and disadvantages of the above-described module are formulated, and conclusions are drawn about possible ways of its application.